Uncertainties in Field Spectroscopy: Operator and Setup Induced Effects on Spectral Radiance Measurements - Carmen Meiller; Andreas Hueni; Reinhard Furrer; Bernhard Schmid; Maria J. Santos (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Field spectroscopy (FS) measurements are crucial for validating Earth observation products obtained on other scales (drone, airborne or satellite). The accuracy of FS measurements relies on sensor traceability to an international standard, operator performance, and the choice of measurement setup. To ensure reliable comparisons of datasets, it is important to quantify the various aspects of uncertainty of FS measurements, which have not yet been thoroughly examined. In this study, we conducted two experiments to assess uncertainties in FS measurements and contribute to a more comprehensive uncertainty budget for in situ measurements. The first experiment examined the impact of varying distances of the fiber optic tip on the reference panel and derived a correction model. The latter was further applied to a case study, showing the impact of different distances to the panel on reflectance factors of vegetation. The second experiment investigated the influence of an operator's presence on the measurements. Results indicate uncertainties of up to 3.4% depending on wavelength and distance, and up to 2% due to the operator's presence. These uncertainties have some influence on the vegetation reflectance factors, and our findings show that without a proper examination of uncertainty, we may misinterpret a variability in the data rather than in the measurement setup. Our results emphasize the importance of estimating the uncertainty driven by operator and setup characteristics in FS. They highlight the need to calculate uncertainty budgets for FS measurements, as they are used to validate other sensors and ultimately influence further derived conclusions.